2016
DOI: 10.1002/path.4808
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix – the under‐recognized element in lung disease?

Abstract: The lung is composed of airways and lung parenchyma, and the extracellular matrix (ECM) contains the main building blocks of both components. The ECM provides physical support and stability to the lung, and as such it has in the past been regarded as an inert structure. More recent research has provided novel insights revealing that the ECM is also a bioactive environment that orchestrates the cellular responses in its environs. Changes in the ECM in the airway or parenchymal tissues are now recognized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
188
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(205 citation statements)
references
References 116 publications
3
188
0
4
Order By: Relevance
“…For the purpose of this review, we will focus on versican and hyaluronan, two interstitial ECM components [3] that can serve as ligands for leukocytes and impact immune and inflammatory responses in lung disease [37]. In addition, we will discuss how specific leukocytes, such as the macrophage, interact with the ECM and the importance of a specific matrix metalloproteinase (MMP), MMP10, in controlling the state of macrophage activation in lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this review, we will focus on versican and hyaluronan, two interstitial ECM components [3] that can serve as ligands for leukocytes and impact immune and inflammatory responses in lung disease [37]. In addition, we will discuss how specific leukocytes, such as the macrophage, interact with the ECM and the importance of a specific matrix metalloproteinase (MMP), MMP10, in controlling the state of macrophage activation in lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the ECM in whole organ regeneration, the source of native lung tissue used to prepare the scaffold can have a direct impact on subsequent regeneration. Several studies have shown that underlying lung pathologies can cause changes in the ECM that are retained following decellularization, and can perpetuate during tissue repair (5). This has been demonstrated for both pulmonary fibrosis and emphysema (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is synthesized by epithelial cells, smooth muscle cells, mast cells, alveolar macrophages and fibroblasts . Fibroblasts are key regulators of extracellular matrix (ECM) proteins and constitute a rich source of growth factors . Interestingly, the vascular mediator prostacyclin may induce VEGF and prostacyclin is synthesized in high amounts by distal lung fibroblasts from severe COPD patients .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Fibroblasts are key regulators of extracellular matrix (ECM) proteins and constitute a rich source of growth factors. 1,17 Interestingly, the vascular mediator prostacyclin may induce VEGF 15 and prostacyclin is synthesized in high amounts by distal lung fibroblasts from severe COPD patients. 18 Our recent data imply that severe COPD patients may have altered fibroblast function and defective repair mechanisms in the ECM structure in response to prostacyclin.…”
Section: Introductionmentioning
confidence: 99%